HANDOUT MAKING TRAINING IN INTEGRATED NATURAL SCIENCE LESSON AT SMP N 43 PADANG - Aulia Afza; Siska Nerita; Annika Maizeli (STKIP PGRI Sumatera Barat, 2021)
The purpose of this community service activity is to provide handout making training in integrated natural science lesson at SMP N 43 Padang. Handout are one of the teaching materials that support the teaching and learning process. Some of the benefits of using handout are helping students not to need to take notes, as a companion to teacher explanations, as student reference material, motivating students to be more active in learning, reminders of the main points of the material taught, providing feedback, and assessing learning outcomes. Therefore, teachers must be able to design handout to help students understand the material before and after the learning process. However, there are still many teachers at SMP N 43 Padang who still do not understand how to properly design handout and have not used handout in the teaching and learning process. The solution offered is that the community service team of Biology Education Study Program lecturers carry out training on making handout for integrated science subjects, where the expertise of the community service team is very supportive in carrying out this activity.